Sustainable Development in the Jordan Valley Final Report of the Regional NGO Master Plan - Kool, Jeroen (Hexagon Series on Human and Environmental Security and Peace,, 2016)
This book summarizes the NGO Master Plan that provides a comprehensive program to rehabilitate the Lower Jordan River and its tributaries in Jordan, Israel and Palestine. It is a regional and civil society effort designed to promote the restoration of the valley's environmental and ecological values within a realistic financial and economic framework. The plan identifies 127 specific regional and national "interventions"(projects) until the year 2050, based on seven strategic planning objectives: pollution control, sustainable water management and river rehabilitation, sustainable agriculture, Jordan River basin governance, ecological rehabilitation, sustainable tourism and cultural heritage development, and urban and infrastructure development. The total investment value is 4.58 billion USD, the plan ranks the interventions and identifies their feasibility in a short, medium and long term investment cycles considering the political environment.